Methodology of Using the Opportunities of Virtual Technologies in the Educational Process (Journal of Pharmaceutical Negative Results, 2022)
Nowadays the content and purpose of education are changing in accordance with the requirements for personnel in society. It is also required that the recipients of education have a high level of competence, as well as modern knowledge. At the same time, along with modern teaching methods, the effective use of technological means is important. Virtual learning technologies are becoming an important factor in solving the educational problems we face today. In the course of our research, methodological aspects of training future specialists in the use of virtual educational technologies were investigated and recommendations were developed.During the research, the methodic features of teaching how to use virtual technology, for future specialists have been studied and recommendations have been created.